Age-Related Gradual Decline in Red blood Cells Indices in Males without Hematological Disorders - Yousaf, Umara; Akhlaq, Sana; Shakeel, Naima; Niaz, Sobia; Latif, Javeria; Irfan, Shazia (Journal of Postgraduate Medical Institute, 2024)
Background: Somatic damage causes the aging process, which raises the chance of mortality. Evaluation of hemoglobin levels in the elderly is a challenging undertaking since it is difficult to determine whether it is decreased due to an underlying disease or simply an effect of advancing age. The study described here was designed to look at how ageing affected peripheral blood parameters in people who had no known hematological disorder. Methods: Data from 88 participants in the age range between 18 and 92 Years with no known hematological disorder were evaluated with particular consideration for hemoglobin, red blood cells count, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration. Four age categories were used to segment the individuals. Group I from 18 to 37 years, group II from 38 to 57 years group III from 58 to 77 years, group IV is 78years onwards. Results: Hemoglobin, red blood cells count, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration in the serum were analyzed. There was a highly significant (p<0.05) difference between hemoglobin, hematocrit and mean corpuscular hemoglobin concentration, among the four groups on comparison with a one-way ANOVA test. These results strongly support the hypothesis that there is a progressive decrease in RBC parameters with advancing age even in the absence of any known illness. Conclusions: RBC parameters varied with increasing age and differed between young males as compared to old age, indicating a decline in erythropoiesis in elderly males.